1999
DOI: 10.1038/sj.ijir.3900437
|View full text |Cite
|
Sign up to set email alerts
|

Gene-polymorphisms of angiotensin converting enzyme and endothelial nitric oxide synthase in patients with erectile dysfunction

et al.

Abstract: Aims of the study: Regulation of the penile smooth muscle tone and contractility is closely related to the activity of vasoactive substances, angiotensin II or nitric oxide. We investigated the relationship between gene polymorphism in the angiotensin converting enzyme (ACE) or endothelial nitric oxide synthase (ecNOS) and development of erectile dysfunction. Methods: In 84 subjects with organic erectile dysfunction and 63 control subjects, gene polymorphisms in the ACE and ecNOS were determined by the polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 19 publications
2
38
0
Order By: Relevance
“…Many vascular diseases are associated with imbalance of Ang II and NO actions. 37 Park et al 39 reported that the deletion of polymorphism in the ACE gene, the DD genotype, as a marker of general vascular disease, may be seen more frequently in men with a diagnosis of vasculogenic erectile dysfunction. It has been suggested that ACE inhibitors might be used in the treatment of vasculogenic ED.…”
Section: Vasoactive Mediators and Erectile Dsyfunction E A Hamed Et Almentioning
confidence: 99%
“…Many vascular diseases are associated with imbalance of Ang II and NO actions. 37 Park et al 39 reported that the deletion of polymorphism in the ACE gene, the DD genotype, as a marker of general vascular disease, may be seen more frequently in men with a diagnosis of vasculogenic erectile dysfunction. It has been suggested that ACE inhibitors might be used in the treatment of vasculogenic ED.…”
Section: Vasoactive Mediators and Erectile Dsyfunction E A Hamed Et Almentioning
confidence: 99%
“…18 This can be a possible explanation of the inconsistency of association between ACE genotype and ED. For example, Park et al 19 examined 84 Korean patients with organic ED and 63 control subjects of the same age and found significantly higher incidence of the DD genotype in the first group compared to the second (54 and 24% respectively). On the other hand, Rosas-Vargas et al 20 have not found such association in Mexican population.…”
Section: Introductionmentioning
confidence: 99%
“…ACE may be in vol ved in the pat ho ge ne sis of erec ti le dysfuncti on be ca u se the ac ti va ti on of an gi o ten sin I to angi o ten sin II re sults in con trac ti on of the pe ni le smo oth musc le, and pre sen ce and func ti on of an gio ten sin II, the an gi o ten sin II re cep tor, and ACE in the cor po ra ca ver no sa. 14,34 Park et al 35 re por ted that the DD ge noty pe might be se en mo re fre qu ently in men with a di ag no sis of vas cu lo ge nic erec ti le dysfunc ti on in a Ko re an po pu la ti on. In anot her study, Ma zo et al 36 fo und that, the pre va len ce of DD genoty pe in the ED gro up was sig ni fi cantly hig her than the non-ED gro up (p< 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they sug ges ted that this as so ci a ti on had a prac ti cal imp li ca ti on that might be con si de red in the de ve lop ment of ED therapy pro to cols ba sed on the sti mu la ti on of pe ni le NO synthe sis. In 1999, Park et al 35 per for med an in ves ti ga ti on on the re la ti ons hip bet we en eNOS4a/b ge ne poly morp hism and ED in a Ko re an po pu la ti on. Ho we ver, the ir re sults fa i led to show a sig ni fi cant cor re la ti on bet we en ED and eNOS4a/b ge ne poly morp hism (p= 0.813).…”
Section: Discussionmentioning
confidence: 99%